Russia in the Arctic : hard or soft power? - Sergunin, Alexander; Konyshev, Valery (Soviet and post-Soviet politics and society ;, 2016)
In this timely book, the authors provide a detailed analysis of Russia's national interests in the Arctic region. They assess Russia's domestic discourse on the High North's role in the system of national priorities as well as of Moscow's bi- and multilateral relations with major regional players, energy, environmental, socio-cultural, and military policies in the Arctic. In contrast to the internationally wide-spread stereotype of Russia as a revisionist power in the High North, this book argues that Moscow tries to pursue a double-sided strategy in the region. On the one hand, Russia aims at defending her legitimate economic interests in the region. On the other hand, Moscow is open to co-operation with foreign partners that are willing to partake in exploiting the Arctic natural resources. The general conclusion is that in the foreseeable future Moscow's strategy in the region will be predictable and pragmatic rather than aggressive or spontaneous. The authors argue that in order to consolidate the soft power pattern of Russia's behavior a proper international environment in the Arctic should be created by common efforts. Other regional players should demonstrate their responsibility and willingness to solve existing and potential problems on the basis of international law.